2008
DOI: 10.3382/ps.2007-00317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monochromatic Light on Immune Response of Broilers

Abstract: A total of 260 one-day-old Arbor Acres male broilers were exposed to red light (RL), green light (GL), blue light (BL), and white light (WL), respectively, by using a light-emitting diode system for 7 wk. There were 5 replicate pens for each light treatment and 13 birds per pen. The effects of monochromatic light on the immune response were studied. The results indicated that proliferation of peripheral blood T lymphocytes in the GL group was significantly increased (by 80.8 and 54.8%) compared with those in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
88
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 30 publications
14
88
0
4
Order By: Relevance
“…No previous reports of light color effects on humoral immunity are available but our results were somewhat similar to those of Xie et al (2008Xie et al ( , 2011 who showed that G and B light increase intestinal intraepithelial lymphocytes, goblet cells, and IgA+ cells in the small intestine, which increases intestinal mucosal immunity in broiler chicks. Brainard et al (1986) reported that light color influences prolactin levels in hamsters, and that prolactin can have regulatory effects on immune functions in mammals (Hermann and O'dorsio, 1991) and birds (Skwarlo-Sonta et al, 1987).…”
Section: Discussionsupporting
confidence: 89%
“…No previous reports of light color effects on humoral immunity are available but our results were somewhat similar to those of Xie et al (2008Xie et al ( , 2011 who showed that G and B light increase intestinal intraepithelial lymphocytes, goblet cells, and IgA+ cells in the small intestine, which increases intestinal mucosal immunity in broiler chicks. Brainard et al (1986) reported that light color influences prolactin levels in hamsters, and that prolactin can have regulatory effects on immune functions in mammals (Hermann and O'dorsio, 1991) and birds (Skwarlo-Sonta et al, 1987).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, triglycerides were significantly higher in birds under R light but lower in those under the B treatment, which may have been due the calming effect of the B treatment on chicken activity (Prayitno et al, 1997), which would decrease blood pressure and reflect on blood GLU and triglyceride levels. IgG concentration and H:L were not significantly affected by most of the light treatments but did increase under B light, which corresponded to the results of Xie et al, (2008).…”
Section: Discussionsupporting
confidence: 83%
“…The quality of the eggs laid by layers exposed to green light were the most affected and was better compared with the other treatments. Xie et al (2008) evaluated the effect of monochromatic LED lighting (red, green, white, or blue) on the immunity of broilers reared up to seven weeks and did not find any differences in antibody titers among birds exposed to blue, green, and white light. The authors concluded that blue and green LED light had a stronger effect in terms of enhancing the immune response compared with red LED light, and that blue LED light may alleviate the response to stress of broilers.…”
Section: Influence Of Artificial Lighting On the Performance And Egg mentioning
confidence: 99%